Synergetic Combination of Carbon Xerogels, Graphene Oxide and nano‐ZnO for Aqueous and Organic Supercapacitors - Coneo Rodriguez, Rusbel (2024)
Three-dimensional carbon xerogels were synthesised via a facile approach that included the use of ZnO nanostructures both as a templating agent and as a catalyst for resorcinol–formaldehyde resin polymerisation simultaneously. Graphene oxide (GO) served as a stabilising agent during the drying and pyrolysis processes, avoiding the collapse of structure and improving the area surface. The method enabled the asobtained materials to possess optimised 3D porous structures for energy-storage devices, such as wires or spaghetti-like structures. Also, a high BET surface area was obtained (1661 m2•g−1) without using an additional activating agent. This great surface area improved the specific capacitance compared to materials without GO (358.1 F•g−1 vs 170.4 F•g−1). The carbon-containing devices derived from resorcinolformaldehyde resin, GO, and Zn oxide showed better performance than the devices without GO. In particular, the sample that contained 2.5% of GO in the synthesis showed a specific capacitance of 166.6 F•g−1 at 0.5 A•g−1 and remained at ∼120 F•g−1 at 5 A•g−1. Also, it showed interesting energy density values at 0.5 A•g−1 (14.8 Wh•kg−1) and a power density of 200.7 W•kg−1. This reveals that the synthesis process made it possible to obtain composite materials with large surface areas without using a supercritical drying process.